Perilaku Harian Pachliopta aristolochiae Betina di Museum Serangga dan Taman Kupu Taman Mini Indonesia Indah (MSTK TMII) - PRASETYO, AGUNG; PERSADA, ALAM PUTRA; AFIFAH, ISMAYATI; DJALIL, VELLA NURAZIZAH; RAFFIUDIN, RIKA (Jurnal Sumberdaya Hayati, 2017)
Pachliopta aristolochiae plays important role in the ecosystems. Their role as pollinators can be observed from their daily behaviors. This study aimed to observe the behaviors of butterfly P. aristolochiae as well as their food preferences on daily basis. This research was conducted at the Museum of insect and butterfly of Taman Mini Indonesia Indah. Observations were done in two female individuals based on scan sampling method. Behavior was observed according to perching, flying, nectaring and interaction activities. Our results indicate that P. aristolochiae mostly showed flying ( 35.9%) and nectaring (30.6%) activities. On the other hand, interaction (9.3%) was among the least behaviors observed during the study. Nectaring activity was mostly shown within 08.00 - 09.40 am, while perching was observed throughout the day within 11.00 - 16.00. During observation, P. aristolochiae was recorded in visiting various plants, including Ixora sp., Hibiscus rosa-sinensis, Clerodendrum japonicum, Ochna serrulata, Jatropha curcas and J. integrifolia.